2017
DOI: 10.1007/s12630-017-0954-5
|View full text |Cite
|
Sign up to set email alerts
|

“Eyeball test” of thermographic patterns for predicting a successful lateral infraclavicular block

Abstract: We conclude that visual evaluation by an eyeball test of specific thermographic patterns of the blocked hands may be useful as a valid and reliable diagnostic test for predicting a successful LIC block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Interestingly, in another study these authors found that blinded observers were able to predict lateral infraclavicular block success with a sensitivity of 92% and a predictive value of 95% based on perceived temperature differences between the corresponding distal phalanges of the 2nd and 5th digits of the blocked and the contralateral hand, rendering it a valid and reliable diagnostic test for predicting successful lateral infraclavicular block . More recently, this group found that visual evaluation of thermographic patterns as well are useful for predicting successful lateral blocks in the clinical setting …”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 99%
“…Interestingly, in another study these authors found that blinded observers were able to predict lateral infraclavicular block success with a sensitivity of 92% and a predictive value of 95% based on perceived temperature differences between the corresponding distal phalanges of the 2nd and 5th digits of the blocked and the contralateral hand, rendering it a valid and reliable diagnostic test for predicting successful lateral infraclavicular block . More recently, this group found that visual evaluation of thermographic patterns as well are useful for predicting successful lateral blocks in the clinical setting …”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 99%
“…2 Will real-time visualization of the onset of distal blocks lead to a similar future? The paper by Andreasen et al in this issue of the Journal on the visual assessment of thermographic patterns to predict the success of a lateral infraclavicular block (LIB) 3 gives us some food for thought.…”
mentioning
confidence: 99%